Theatre-for-Development as Information Panacea for Rural Dwellers in Nigeria during a Pandemic: Lessons from COVID-19 - Okwuowulu, Charles; Stevenson, Osakue Omoera; Onyemuchara, Casmir; Akoh, Ameh Dennis; Emokpae, Charles; Akpa, Christopher; Chinda, Michael (The Journal of Society and Media, 2023)
The subject of COVID-19 (coronavirus) in Nigeria emerged with various misrepresentations and conspiracy theories, such as the notion of COVID-19 as a forerunner of the Anti-Christ or the commencement of a ’New World Order’ occasioned by the 5G network. COVID-19 information in Nigeria was managed by the Presidential Task Force through daily media briefings. This paper examined the PTF’s information dissemination structure and its impact on four indigenous communities in south-eastern Nigeria: Ikwo in Ebonyi State, Iva-Valley Forestry Hill Camp 1 in Enugu State, Umualumu Old Road in Imo State, and Ogbagu Obukpa in Enugu State. TfD was used during lockdown to inform indigenous communities and promote necessary health precautions. The project used TfD and Brecht’s Epic Theatre Theory in 4 Nigerian communities to show how TfD can complement other media in informing rural residents about COVID-19. TfD mobilized indigenous communities in southeastern Nigeria to understand Igbo and take COVID-19 precautions despite PTF’s robust information dissemination structure. TfD could have helped the PTF share vital COVID-19 info with rural communities in Nigeria. The Nigerian government should establish a robust infrastructure for raising awareness and combating COVID-19 and other pandemics in rural areas through TfD